Analisis Anggaran Biaya Operasional Dan Anggaran Pendapatan Terhadap Kinerja Keuangan Berdasarkan Return On Asset (ROA) Pada Counter Crocs TM Di Kota Malang - Febriana Maria Luan; Luh Dina Ekasari; Ahmad Mukoffi (JURNAL MUTIARA AKUNTANSI, 2021)
The purpose of this research is to find out the operational budget and revenue budget affect the level of financial performance at the crocs tm counter in Malang City. The design of this research is to use a quantitative descriptive method, in this research the data sources used are secondary data and primary data. The data collection techniques used in this research are interviews and observation. The data analysis technique used is quantitative descriptive analysis. It was found in the results of this research that operational variables can have a significant effect on the change ratio, while the revenue budget has no significant effect on the change ratio in Counter Crocs TM in Malang City, Malang City